Regenerating physiotherapy curriculum in higher education: diving into planetary health and service-learning conceptual synergies - Berta Paz-Lourido; Álvaro Ribeiro-Chaves (Frontiers in Public Health, 2025)
The physiotherapy curriculum has been modified over the years to address patients, community and health care system needs more fittingly. Recent attention is being paid to the need for an eco-social transition of the profession. This article delves into conceptual frameworks that underpin the urgent need to regenerate the curriculum, fostering a vision of humanity and the planet as deeply interconnected and indivisible. This implies not only becoming aware of the environmental impact of educational and clinical physiotherapy practices but also to reframe education through the lenses of planetary health. This calls for active engagement, a solution-oriented approach to education, and a reimagining of humanity’s relationship with the planet. Service-learning operates as an experiential critical pedagogy, blending hands-on engagement with reflective analysis to challenge students’ assumptions and foster transformative learning rooted in social justice. This form of experiential critical pedagogy empowers students to learn while serving their communities in a range of areas—most notably in response to the urgent challenges of planetary health. By aligning planetary health with service-learning—an action-based pedagogy that cultivates student empowerment and civic responsibility—we can envision a regenerative transformation of the physiotherapy curriculum. This work’s aim is to gain epistemological insight on the social-ecological complexity on this matter. The article discusses four rationales that permeate a framework for this regenerating purpose in the light of the Global Action Plan on climate change and health. It tackles planetary health, higher education, physiotherapy, and service-learning as a pedagogy orientated to action and critical reflection. All this opens the gate to rethink the role of physiotherapy education in the Anthropocene. Higher education needs to interconnect individuals, communities, and the natural world, promote shared governance and democracy, stimulate critical thinking and embrace diversity. Education in physiotherapy needs to underscore cognitions and academic proficiency, emotional intelligence, social consciousness, and ethical awareness, matchmaking learning experiences with local and global challenges. There is a need to advocate for pedagogical approaches that inspire hope and prepare students to contribute meaningfully to their communities, upholding principles of equity and intergenerational justice.